Prediction of nanoparticle transport behavior from physicochemical properties: machine learning provides insights to guide the next generation of transport models1. Issue 4 (30th August 2015) - Goldberg, Eli; Scheringer, Martin; Bucheli, Thomas D.; Hungerbühler, Konrad
<x xml:space="preserve">Abstract</x> Machine-learning methods are used to identify factors that govern transport of nanoparticles in column experiments.